Workplace mistreatment in the hospitality and tourism industry: A systematic literature review and future research suggestions. (December 2021) - Zhou, Yuan; Mistry, Trishna G.; Kim, Woo Gon; Cobanoglu, Cihan
Abstract: This study conducts a systematic review and examines 156 articles of workplace mistreatment in hospitality and tourism industry, published from Web of Science and Scopus. The findings reveal six main concepts of mistreatment with several research themes from the existing literature, and further explicates their triggers and consequences. It also depicts various theories and models used in the referred articles. The article excavates and discusses several key research gaps in the research on workplace mistreatment in the hospitality and tourism industry for future research directions.